First Report of Plectosphaerella pauciseptata Associated with Tomato Root Rot Disease in China - Chen, Zeshun; Chen, Yunyun; Zhou, Yueyan; Chen, Pengzhao; Zhang, Wei; Liu, Mei; Yan, Jiye; Wang, Chenfang (Plant disease, 2025)
Tomato (Solanum lycopersicum) is widely grown worldwide, ranking first among vegetable crops. Root diseases of tomatoes can cause serious yield losses. In June 2023 and 2024, tomato root rot symptoms were observed in the greenhouse with 70%-90% incidence approximate number of plants (N=210) in Beizhen City (121°47 ' 30 ''E, 41°35' 45 ''N), Liaoning Province, China. In 2024, the same symptoms were observed in the greenhouse in Shunyi City (116°39 ' 41 ''E, 40°09' 00 ''N), Beijing Province. Initially tomato leaves turned yellow, followed by wilting and withering of the entire plant. Roots and stems of the plants exhibited brown necrosis. Infected root tissues from six individual plants in each of two distinct regions were cut into 24 small fragments (5 × 5 mm) at the interface between healthy and symptomatic root tissue and surface sterilized with 2% NaOCl for 2 min followed by 75% ethanol for 30 s, rinsed five times with sterile water, and placed on potato dextrose agar (PDA). After 3-6 days of incubation at 25℃, hyphal tips from the edges of colonies were transferred to new PDA plates. Nine morphologically similar fungal isolates (JZB3540002-JZB3540010) were obtained from diseased samples. Six days old colonies on PDA were dense, mycelium appressed, white and the reverse was white to light yellow-brown. Conidiophores were straight or flexuous, unbranched, smooth, and had an elliptical apex. Conidia were elliptical, apex rounded, aseptate, and multi-guttulate. Conidia were 6 to 12 × 2 to 5 µm (average 7.70 × 2.95 µm, n=30). Following 14 days of incubation, colonies were hyaline with white mucilaginous masses, and aerial hyphae appeared at the center of the colony (Carlucci et al. 2012; Usami et al. 2012; Yang et al. 2021). For molecular phylogenetic analysis, genomic DNA was extracted from the nine isolates, and the internal transcribed spacer (ITS) region, large subunit 28S rDNA (LSU) and translation elongation factor 1 alpha (TEF-1alpha) gene were amplified using ITS1/ITS4 (White et al. 1990), LROR/LR5 (Vilgalys and Hester 1990), and EF-688F/EF-1251R (Alves et al. 2008) primers respectively. BLAST results indicated that the ITS, LSU, and TEF sequences showed 98 to 100% identity with Plectosphaerella pauciseptata type specimens sequences at NCBI (GenBank KY399823, KY662250, and KY421321). Maximum likelihood (ML) inference phylogenetic tree was constructed to confirm the identity of the nine strains. ML tree reveals that the nine strains clustered with Plectosphaerella pauciseptata with 100% bootstrap support value. Sequence data were deposited in NCBI GenBank with accession numbers PP716848 and PQ621101-PQ621108 (ITS), PP717077 and PQ621369-PQ621376 (LSU), and PQ629447-PQ629455 (TEF). To confirm pathogenicity, roots of 18 three-leaf-stage cultivar 'Ying fen 8' tomato seedlings were wounded and dipped in 50 ml conidial suspension (107 conidia/ml) or sterile water (control) for 30 min. Tomato seedlings were transplanted into new pots and placed in the greenhouse at 22℃(night)/25℃ (day) with natural daylight. After 25 days, inoculated plants had symptoms similar to naturally infected plants, and no symptoms were observed in the control plants. Plectosphaerella pauciseptata was re-isolated from the base of the roots of inoculated tomatoes, and the identification was confirmed based on morphological characteristics and DNA sequence analysis, The experiment was repeated three times with similar results. Plectosphaerella pauciseptata has been reported causing tomato root rot in Italy (Raimondo and Carlucci 2018), however, to our knowledge, this is the first report of P. pauciseptata causing tomato root rot in China. This study provides insight into the root diseases of tomatoes and provides the basis for further investigations to assess and implement effective disease management strategies.